2017
DOI: 10.3390/rs9111117
|View full text |Cite
|
Sign up to set email alerts
|

Fire Regimes and Their Drivers in the Upper Guinean Region of West Africa

Abstract: Abstract:The Upper Guinean region of West Africa exhibits strong geographic variation in land use, climate, vegetation, and human population and has experienced phenomenal biophysical and socio-economic changes in recent decades. All of these factors influence spatial heterogeneity and temporal trends in fires, but their combined effects on fire regimes are not well understood. The main objectives of this study were to characterize the spatial patterns and interrelationships of multiple fire regime components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…Our study showed different results for the N'Zi River Watershed, underlining an opposite trend for wildfire occurrence. Similar results have been found in West Africa, identifying decreasing trends in both number of wildfires and burnt areas during recent decades [58,59]. Andela et al [60] showed a significant decreasing trend in the number of fires, size of fires and burnt area in Africa in the period 2003-2015 using MODIS fire data.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our study showed different results for the N'Zi River Watershed, underlining an opposite trend for wildfire occurrence. Similar results have been found in West Africa, identifying decreasing trends in both number of wildfires and burnt areas during recent decades [58,59]. Andela et al [60] showed a significant decreasing trend in the number of fires, size of fires and burnt area in Africa in the period 2003-2015 using MODIS fire data.…”
Section: Discussionsupporting
confidence: 66%
“…The inclusion of different environmental and biophysical covariates might improve the GAM results. For instance, fire activity is most strongly influenced by climate, topography [76], vegetation type and population density [59]. It is therefore important to collect data on potentially influential covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the African savannas, the most extreme fire conditions (annual burning, high rainfall) occur in the Guinean forest −savanna mosaic ecoregion, extending over 670 000 km 2 in West Africa (Kier et al 2005). In this area, fire return interval is generally between 1 and 3 years, with 21% of this area burned annually (Innes 1972, Dwomoh andWimberly 2017). Annual rainfall is in the range of 1000 −1600 mm yr -1 (L'Hôte and Mahé 2012), yielding very high grass production .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fire use is perceived as an integral practice in most rural savannas around the world that needs attention. Several studies have shown fire effects on the environment (Dwomoh and Wimberly 2017;Nyongesa and Vacik 2018). Author observation of twenty-five years living in the savanna region of Ghana, shows the widespread use of fire in this ecological zone.…”
Section: Background and Setting Of The Study Areamentioning
confidence: 99%
“…In fire-prone West African savannas, the use of fire is integral in socio-cultural practices that are important for rural livelihoods and socio-economic activities (Rose Innes 1972;Archibald and Bond 2003;Dwomoh and Wimberly 2017). Nonetheless, the savannas provide the land resources where the bulk of cereals, grains and livestock are produced, usually by means of traditional methods of agriculture where fire is used to clear the land of vegetation for cropping, to burn stubble after harvest, as well as for weed management (Amissah, Kyereh and Agyeman 2010;Nyongesa and Vacik 2018).…”
Section: Introductionmentioning
confidence: 99%